STRENGTHENING THE CAPACITY OF MOSQUE ADMINISTRATORS IN UTILIZING DIGITAL TECHNOLOGY TO ENHANCE THE COMMUNITY'S ISLAMIC ECONOMY - Silvy Windha Mediaswari; Mohamad Akbar F. Ibrahim; Martno Mohamad Dumbela; Yuliyanti Suleman; Rahman Erama; Rizky Amelia Wibowo; Riya Andriyani Ahmad (LPPM Universitas Flores, 2026)
Mosques play a strategic role as centres of worship, education, social activity, and community economic empowerment. However, some mosque administrators still face limitations in utilizing digital technology for administration, financial transparency, infaq services, and the strengthening of congregational businesses. This community service activity aimed to enhance the capacity of mosque administrators in using simple digital technologies to support the strengthening of the community-based Islamic economy. The activity employed a participatory approach through needs identification, socialization, technical training, guided practice, and evaluation. The participants were 30 administrators of Sabilulhuda Boki Owutango Mosque in Kota Timur District, Gorontalo City. The materials covered mosque digital literacy, cloud-based document management, and the use of QRIS-based digital payments for infaq and sadaqah. The results showed an increase in participants’ understanding, from an initial average score of 2.56 to 4.84 in the final evaluation. The outputs of the activity included a digital mosque cashbook format, forms for collecting data on congregants and their businesses, a design for the mosque’s digital information channel, and a simple catalogue of congregational businesses. This activity demonstrates that practice-based digital training can strengthen the capacity of mosque administrators to manage institutional services in a more orderly, transparent, and adaptive manner. Further mentoring is needed to ensure that mosque digitalization does not stop at technical mastery of digital tools but develops into a sustainable Islamic economic empowerment system.